Відповідальність судновласника за забруднення морського середовища нафтопродуктами внаслідок умисного зливу - Фурман, М. О.; Furman, Maryia; Фурман, Мария (Одеса : Гельветика, 2019)
Статтю присвячено питанням нормативно-правового регулювання відповідальності судновласника за забруднення морського середовища нафтопродуктами. Проведено аналіз міжнародних норм, які регулюють питання відповідальність за забруднення. Автор доходить до висновку, що норми, які регламентують правила та порядок експлуптації суден, зливу залишків нафтопродуктів з танків, бункерувальні операції, а також інші маніпуляції, пов’язані з нафтовмісткими речовинами, прописані у законодавстві дуже чітко, та можна зробити висновок, що проблема у кількості порушень у цій сфері пов’язана, насамперед, з необізнаністю осіб щодо масштабів шкоди, яку вони завдають своїми діями, тому, представляється доцільним проведення спеціалізованих тренінгів для екіпажів суден та берегового персоналу. Також слід застосовувати більш суворі санкції до порушників, наприклад позбавлення (на певний строк або безстроково) права обіймати певну посаду. The article is about regulatory issues of and legal regulation of the shipowner’s liability for the pollution of the marine environment with oil products. The analysis of international standards that regulate the question of responsibility for pollution. With the growth of urbanization and industrialization, the marine environment is increasingly exposed to a negative human impact, which is causes so-called degradation of the marine environment. It means that the sea spaces lose their initial condition, polluted with different wastes, become a landfill for tons of industrial waste, toxic substances, it also refers to the inappropriate use of the “wealth” of the World Ocean. Many of the “active users” of the sea spaces of our planet simply underestimate the significance of the above in the life of all mankind. Perhaps this is why the attitude to the seas and oceans is so disreputable. The degradation of the marine environment may be associated with a number of sources, including shipping and maritime activity. Every year in consequence of accidents and illegal discharges about 600,000 tons of oil come into the oceans. Despite numerous measures to improve the safety of the use of the marine environment, the rules are violated, vessels that are not suitable for operation, and, moreover, they transport very harmful goods to the environment. The negligence in such sphere leads to the widescale damage of the environment that can not always be eliminated entirely and it is horrible whilethat those who responsible for causing damage often avoid responsibility. The purpose of the article is to consider the question of liability and problem of reimbursement of damages to the environment caused by pollution with petroleum products on the basis of international norms governing this area of relations. Legal liability is just one of the many legal instruments used to prevent degradation of the oceans, but it is urgently needed to increase its efficiency, becaus the welfare of all living is at stake. Since being so vast and significant, the marine environment is under threat and definitely requires careful attitude and protection.
Фурман М. О. Відповідальність судновласника за забруднення морського середовища нафтопродуктами внаслідок умисного зливу / М. О. Фурман // Lex Portus : юрид. наук. журн. / редкол. : С. В. Ківалов (голов. ред. ради), Б. А. Кормич (голов. ред.), Т. В. Аверочкіна (наук. ред., відп. секр.) [та ін.] ; НУ "ОЮА", ГО "МА Святий Миколай". - Одеса : Видавничий дім «Гельветика», 2019. - № 2. – C. 70 - 79.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE; відповідальність судновласника; конвенція; забруднення навколишнього середовища; компенсація; ответственность судовладельца; загрязнение окружающей среды; shipowner responsibility; environmental pollution